A colorimetric chemosensor for the sequential detection of copper ion and amino acids (cysteine and histidine) in aqueous solution1. Issue 39 (2nd May 2015) - Kim, Yong Sung; Park, Gyeong Jin; Lee, Seul Ah; Kim, Cheal
<x xml:space="preserve">Abstract</x> A simple and selective colorimetric chemosensor was reported for the sequential detection of Cu2+, cysteine and histidine.